Evaluating the Safety and Efficacy of SGLT-2 Inhibitors on Reducing Cardiovascular and Renal Mortality, Morbidity and Inflammatory Outcomes in Various Patient Populations: A Systematic Review and Meta-Analysis of 92 920 Patients - Syed Hamza Haider; Areeka Irfan; Samir Mustafa Sheikh; Muhammad Omar Larik; Alishba Raza; Yumna Khabir (Clinical Medicine Insights: Cardiology)
Background: The effect of Sodium Glucose Co-Transporter 2 inhibitors on cardiovascular, renal, dyslipidemia, and inflammatory markers has not been analyzed simultaneously. The goal is to determine if SGLT2 inhibitors significantly reduce cardiovascular and renal mortality, and improve these health outcomes. Methods: PubMed, Cochrane Library and MEDLINE databases were used to conduct a comprehensive literature search from inception to September 2023. Randomized control trials with follow-up for at least 8 weeks, with a group taking SGLT2 inhibitors being compared with a group taking either placebo or other medication, in which cardiovascular outcomes, renal outcomes, lipid biomarkers, and inflammatory markers were reported as the primary outcomes were included. The statistical analyses were conducted using Review Manager with a random-effects model. Results: Thirteen studies comprising 92 920 patients were analyzed for several outcomes. The analysis revealed a significant reduction in overall mortality, death due to heart failure, cardiovascular causes, and renal causes in the SGLT2 inhibitor group as compared to placebo. Pooled results also revealed a significant reduction in the frequency of renal replacement therapy and renal composite endpoint in patients on SGLT2 inhibitors. There was also a significant reduction in IL-6, TNF-a, systolic blood pressure in the same group. On the other hand, Flow Mediated Dilation (FMD), lipid profile, and the incidence of amputations and fractures showed no significant associated SGLT2 inhibitor therapy. Conclusion: Our analysis indicates that diabetics and non-diabetics suffering from cardiovascular and renal diseases experience a significant reduction in morbidity and mortality from SGLT2 inhibitor therapy, leading to a better prognosis of such conditions in the long-term.